CLINICAL-LABORATORY, IMMUNOLOGICAL, PATHOGENETIC MANIFESTATIONS OF ANTIPHOSPHOLIPID SYNDROME AND IDENTIFICATION OF EFFECTIVE TREATMENT REGIMENS (REVIEWS) - Musakov Mirzokhid Sabitdjanovich; Samatova Lobar Dilmurodovna; Turaxojaeva Sabokhat Sultanshikovna; Salaeva Muborak Saidabdullayevna; Tursunova Minavvar Ulug’bekovna (Journals Park Publishing, 2023)
Antiphospholipid syndrome (APS) is one of the leading causes of thrombosis. According to some estimates, the incidence of APS is about 5 new cases per 100,000 people per year and the prevalence is about 40-50 cases per 100,000 people [1], thus the problem of APS remains one of the most important in medicine.
Keywords: antiphospholipid syndrome (APS), antiphospholipid antibodies, lupus anticoagulant.